Effect of Light Intensity and Handling During Rearing on Broiler Breast Meat Characteristics - McKee, N.A.; Lien, R.J.; Hess, J.B.; Bilgili, S.F.; McKee, S.R. (International Journal of Poultry Science, 2009)
This study was designed to evaluate the effects of light intensity and handling during rearing on broiler and meat quality factors. Male broilers were housed in light-tight rooms and subjected to Bright (BL) [15.0 Foot-Candles (FC)] or Dim (DL) (0.1 FC) intensity. To determine effects of handling on meat quality, birds were further divided into 3 handling groups either handling by Legs (L) or Wings (W), or No Handling (NoH). After processing and chilling at 51 d of age, breast filets were deboned at 2 h and 4 h PM and filet weights, filet dimensions (length, width, height and area), sarcomere length, cook-loss and tenderness were evaluated. Birds subjected to DL had greater live weights (p